Penerapan Resilience Finance dan Resistnance Finance Terhadap Laporan Keuangan Yang Menekankan Pada Kemampuan PT Paninvest Tbk Untuk Bertahan dan Pulih - Nurul Laily; Avita Anggraeni; Rista Intan Pertama Sari; Maria Yovita R.Pandin (BADAN PENERBIT STIEPARI PRESS, 2024)
This research data is obtained from the web based on the financial statements of PT Paninvest Tbk to determine the effect between financial resilience and financial resistance by analyzing financial statement data that occurred in 2022. We (researchers) use quantitative data in this study, namely by analyzing the report data we get so that we as researchers can present PT Paninvest Tbk's financial statements in a journal entitled